A correlation study of fluorouracil pharmacodynamics with clinical efficacy and toxicity. Issue 3 (June 2018) - Esin, Ece; Telli, Tugba Akin; Yuce, Deniz; Yalcin, Suayib
Purpose: Plasma 5-fluorouracil (5-FU) concentrations vary greatly between individuals who have received standard dosage. Pharmacokinetic adjusted doses have been hypothesized to overcome the possibility of potential toxicity and ineffectiveness related to inappropriate plasma levels of 5-FU. In this study, we prospectively investigated the clinical benefit and toxicity of 5-FU in relation to its pharmacokinetic properties. Methods: Pharmacokinetics, effectiveness, and toxicity of 5-FU were investigated in 101 patients. The 5-FU pharmacokinetics were measured on day 2 of chemotherapy infusions. Clinicodemographic characteristics are outlined. Results: All 101 patients who received adjuvant chemotherapy were alive at the end of a median 45 months of the follow-up period. At least one grade 1 adverse event (AE) was observed in 69.3% of the patients and grade two AEs were observed in 10.1% of the patients. The 5-FU levels ranged between 103 and 4311 µg/L and area under the curve (AUC) measurements ranged between 4.5 and 189.7 mg min/L. Pharmacokinetic measurements were not significantly correlated with clinical efficacy (log-rank p = 0.21). However, higher AUC levels were positively correlated with toxicity (p = 0.02) and with the severity of adverse events. The risks of mucositis (odds ratio [OR] 1.45; p = 0.042) and neurotoxicity (OR 2.01; p = 0.009) were significantly increased in a logistic regression model. Conclusions: There is no clear evidence that increased plasma levels or pharmacokinetic adjusted doses of 5-FU were related to better efficacy. However, toxicity might be closely associated with increased plasma levels of 5-FU. Toxicities can be deferred via dose adjustments without any expense in efficacy.